Innovation driving economic growth in Malaysia and Indonesia - Mohd Aris, Aslizah; Pazla, Roni (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Malaysia and Indonesia are strengthening their positions in the global market by prioritizing innovation as a key driver of sustainable economic growth. However, both countries face challenges such as limited financing and talent shortages. This discussion highlights how the two nations promote innovation, address these obstacles, and shape their strategies toward economic transformation.